Differences in growth and vascularization of ectopic menstrual and non-menstrual endometrial tissue in mouse models of endometriosis. Issue 8 (10th June 2021) - Nenicu, A; Yordanova, K; Gu, Y; Menger, M D; Laschke, M W
Abstract: STUDY QUESTION: Is there a difference in the growth and vascularization between murine endometriotic lesions originating from menstrual or non-menstrual endometrial fragments? SUMMARY ANSWER: Endometriotic lesions developing from menstrual and non-menstrual tissue fragments share many similarities, but also exhibit distinct differences in growth and vascularization, particularly under exogenous estrogen stimulation. WHAT IS KNOWN ALREADY: Mouse models are increasingly used in endometriosis research. For this purpose, menstrual or non-menstrual endometrial fragments serve for the induction of endometriotic lesions. So far, these two fragment types have never been directly compared under identical experimental conditions. STUDY DESIGN, SIZE, DURATION: This was a prospective experimental study in a murine peritoneal and dorsal skinfold chamber model of endometriosis. Endometrial tissue fragments from menstruated (n = 15) and non-menstruated (n = 21) C57BL/6 mice were simultaneously transplanted into the peritoneal cavity or dorsal skinfold chamber of non-ovariectomized (non-ovx, n = 17), ovariectomized (ovx, n = 17) and ovariectomized, estrogen-substituted (ovx+E2, n = 17) recipient animals and analyzed throughout an observation period of 28 and 14 days, respectively. PARTICIPANTS/MATERIALS, SETTING, METHODS: The engraftment, growth and vascularization of the newly developing endometriotic lesions were analyzed by means of high-resolution ultrasound imaging, intravital fluorescence microscopy, histology and immunohistochemistry. MAIN RESULTS AND THE ROLE OF CHANCE: Menstrual and non-menstrual tissue fragments developed into peritoneal endometriotic lesions without differences in growth, microvessel density and cell proliferation in non-ovx mice. Lesion formation out of both fragment types was markedly suppressed in ovx mice. In case of non-menstrual tissue fragments, this effect could be reversed by estrogen supplementation. In contrast, endometriotic lesions originating from menstrual tissue fragments exhibited a significantly smaller volume in ovx+E2 mice, which may be due to a reduced hormone sensitivity. Moreover, menstrual tissue fragments showed a delayed vascularization and a reduced blood perfusion after transplantation into dorsal skinfold chambers when compared to non-menstrual tissue fragments, indicating different vascularization modes of the two fragment types. To limit the role of chance, the experiments were conducted under standardized laboratory conditions. Statistical significance was accepted for a value of P < 0.05. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Endometriotic lesions were induced by syngeneic tissue transplantation into recipient mice without the use of pathological endometriotic tissue of human nature. Therefore, the results obtained in this study may not fully relate to human patients with endometriosis. WIDER IMPLICATIONS OF THE FINDINGS: The present study significantly contributes to the characterization of common murine endometriosis models. These models represent important tools for studies focusing on the basic mechanisms of endometriosis and the development of novel therapeutic strategies for the treatment of this frequent gynecological disease. The presented findings indicate that the combination of different experimental models and approaches may be the most appropriate strategy to study the pathophysiology and drug sensitivity of a complex disease such as endometriosis under preclinical conditions. STUDY FUNDING/COMPETING INTEREST(S): There was no specific funding of this study. The authors have no conflicts of interest to declare.